The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1155/2013/256025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Susceptibility Pattern of Clinical Nocardia Species: Emergence of Nocardia crassostreae as an Agent of Invasive Nocardiosis

Abstract: The present study is the first report on N crassostreae as a human pathogen. The detection of multidrug-resistant species necessitate molecular identification and susceptibility testing, and should be performed for all Nocardia infections. Nocardiosis manifests various clinical features depending on the Nocardia species and underlying conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, other environmental factors such as reduced water circulation of superficial embayments, warmest temperatures and great nutrient levels can also increase the prevalence of infection of nocardiosis ( Bower et al, 2005 ) as also reported in the PN station as showed by Chl-a values. Interestingly, recent reports assessed for the first time infection of N. crassostreae as emerging human pathogen causing invasive pulmonary nocardiosis in immunosuppressed and immunocompetent patients ( Taj-Aldeen et al, 2013 ; Igbaseimokumo et al, 2016 ). This data suggest N. crassostreae to be a possible emerging disease with consequent possible risk of zoonotic infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, other environmental factors such as reduced water circulation of superficial embayments, warmest temperatures and great nutrient levels can also increase the prevalence of infection of nocardiosis ( Bower et al, 2005 ) as also reported in the PN station as showed by Chl-a values. Interestingly, recent reports assessed for the first time infection of N. crassostreae as emerging human pathogen causing invasive pulmonary nocardiosis in immunosuppressed and immunocompetent patients ( Taj-Aldeen et al, 2013 ; Igbaseimokumo et al, 2016 ). This data suggest N. crassostreae to be a possible emerging disease with consequent possible risk of zoonotic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, molecular methods with sufficient specificity and sensitivity should be employed. Morphological, physiological, and molecular characteristics can play a crucial role to identify Nocardia species (20). While no valuable standard therapy is available for nocardiosis, surgical excision is successfully applied in a number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…According to the difference in the susceptibility pattern of each member of the Nocardia asteroides complex, it can be concluded that prescription of effective antibiotics should be after the accurate identification of the causative Nocardia species. Also, clinical studies showed that some Nocardia species such as Nocardia otitidiscaviarum and Nocardia beijingensis could cause systematic infections, while other species like Nocardia brasiliensis cause limited local infections [1,[6][7]. Trimethoprim-sulfamethoxazole, amikacin, and imipenem are usually the first drug choices for nocardiosis [7].…”
mentioning
confidence: 99%
“…Also, clinical studies showed that some Nocardia species such as Nocardia otitidiscaviarum and Nocardia beijingensis could cause systematic infections, while other species like Nocardia brasiliensis cause limited local infections [1,[6][7]. Trimethoprim-sulfamethoxazole, amikacin, and imipenem are usually the first drug choices for nocardiosis [7]. However, the rate of fatality among patients with pulmonary and brain abscess who consumed trimethoprim-sulfamethoxazole ranged from 20 to 50% [8].…”
mentioning
confidence: 99%